Professional assembly language - Blum, Richard, 1962- (Wrox professional guides., 2005)
Unlike high-level languages such as Java and C++, assembly language is much closer to the machine code that actually runs computers; it's used to create programs or modules that are very fast and efficient, as well as in hacking exploits and reverse engineeringCovering assembly language in the Pentium microprocessor environment, this code-intensive guide shows programmers how to create stand-alone assembly language programs as well as how to incorporate assembly language libraries or routines into existing high-level applicationsDemonstrates how to manipulate data, incorporate.